A scientist in interdisciplinary team-teaching in an English for Research Publication Purposes classroom: Beyond a "cameo role". Issue 40 (July 2019) - Li, Yongyan; Cargill, Margaret; Gao, Xin; Wang, Xiaoqing; O'Connor, Patrick
Abstract: Interdisciplinary collaboration, i.e., collaboration between language professionals and content specialists, has long been called for as a valuable mechanism for supporting students' academic literacy development. Nevertheless, such partnership, in particular in the form of classroom team-teaching, has been rarely found; and the role of content specialists in a team-taught classroom setting is little known. In this paper, we report an observational case study of how an English-speaking scientist (ecologist) engaged in team-teaching with a language instructor, his long-term collaborator, in an English for Research Publication Purposes (ERPP) course for research students in agronomy at a Chinese university on a teaching visit. Our dataset consisted of 16h of video-recorded classroom team-teaching sessions, observational fieldnotes, and interview data. The data analysis revealed three key dimensions of the scientist's instruction: putting "a scientific spin" on the lecture, advising the novices to do what a scientist does, and illuminating the identity of a scientist. Our study offers a valuable reference for practitioners and administrators who may want to foster interdisciplinary collaboration in their institutional contexts and in particular discipline specialists' active participation in teaching ERPP.